Self‐Reported Oral Health‐Related Quality of Life and Orofacial Esthetics Among Young Adults With Treated Dental Trauma - Mari Louise Odersjö; Lina Johansson; Agneta Robertson; Nina Sabel (Clinical and Experimental Dental Research)
ABSTRACT Objectives This study aimed to explore how young adults with a history of dental trauma and restored teeth perceive their oral health–related quality of life (OHRQoL) and orofacial esthetics, with a focus on gender‐based differences. Materials and Methods This pilot study is a retrospective case–control study. Young adults experiencing dental trauma and consequently receiving dental treatment were asked to answer CPQ11‐14, Oral Esthetic Scale (OES), and some complimentary questions concerning the esthetics of their teeth. A control group was recruited. t‐Test was used to analyze the scores of CPQ11‐14 and OES, comparing both the study group and the control group, as well as assessing differences between the genders. Regression analysis ANOVA was used to examine the relationship between the OES questions and CPQ11‐14 domains. Results The study group comprised 74 individuals (mean age = 23 years, SD 2.8), including 48 females and 26 males, with an equivalent number in the control group (mean age = 23 years, SD 3.4), with 49 females and 25 males. The mean score of the CPQ11‐14 was 8.8 (SD 7.2) for the study group and 8.0 (SD 6.8) for the control group. Within the emotional well‐being domain, the study group exhibited a higher mean score (3.4, SD 3.6) compared to the control group (1.5, SD 2.6) (p < 0.001 t‐test). Females in the study group scored higher in the emotional well‐being domain (4.0, SD 3.7) compared to females in the control group (1.8, SD 2.7), (p < 0.01 independent t‐test). The study group, who reported low satisfaction with their tooth color or alignment in the OES, also scored higher in the social well‐being domain of CPQ11‐14 (p < 0.026, ANOVA). This was not observed in the control group. Conclusions Young adults with treated dental trauma trend to report a negative impact on their oral health‐related quality of life and oral esthetics, particularly females.